2019
DOI: 10.1002/anie.201909151
|View full text |Cite
|
Sign up to set email alerts
|

Titanium‐Mediated Synthesis of Spirocyclic NH‐Azetidines from Oxime Ethers

Abstract: The TiIV‐mediated synthesis of spirocyclic NH‐azetidines from oxime ethers using either an alkyl Grignard reagent or terminal olefin ligand exchange coupling partner is described. Through a proposed Kulinkovich‐type mechanism, a titanacyclopropane intermediate forms and serves as a 1,2‐aliphatic dianion equivalent, inserting into the 1,2‐dielectrophilc oxime ether to ultimately give rise to the desired N‐heterocyclic four‐membered ring. This transformation proceeds in moderate yield to furnish previously unrep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Not surprisingly, poly-substituted 1-azaspiro [3.3]heptanes were known in the literature. 9 , 10 We needed, however, a modular approach that would produce compounds with only one substituent (one exit vector) at the core without additional (poly)substitution (Figure 1b). From the structural standpoint, we hoped that such compounds could mimic the mono-substituted piperidines.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, poly-substituted 1-azaspiro [3.3]heptanes were known in the literature. 9 , 10 We needed, however, a modular approach that would produce compounds with only one substituent (one exit vector) at the core without additional (poly)substitution (Figure 1b). From the structural standpoint, we hoped that such compounds could mimic the mono-substituted piperidines.…”
Section: Designmentioning
confidence: 99%
“…Various substituted alkenes, most of which were obtained by the Wittig reaction of the corresponding cyclobutanones, were tested. Indeed, alkyl (4), aryl (5,6), dialkyl (7)(8)(9)(10), and benzyloxy (11) alkenes were compatible with the two-step cycloaddition/reduction sequence, and β-lactams 4-11 were easily obtained (Scheme 2). 19 Lactams containing the CO2Me-group underwent reduction into water-soluble amino alcohols 12a-14a that were N-protected into N-Boc amino alcohols Boc-(12a-14a) to ease the product isolation.…”
Section: Synthesismentioning
confidence: 99%
“…While Paternò–Büchi-type reactions are known to be suitable for polysubstituted four-membered heterocycles, structural requirements are necessary to facilitate photoactivation . There are other synthetic methods to construct oxetane and/or azetidine such as ring-expansion using ylide, β-lactam reduction, C–H bond amination, and Ti VI -mediated spirocyclic azetidine synthesis . Overall, the synthesis of less hindered oxetanes or azetidines is facile owing to classical intramolecular displacement reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium enolates, prepared directly from their enolizable carbonyl precursors, act as an important nucleophile in the addition to aldehydes, ketones, and imines . Furthermore, organotitanium has been widely used in the hydroamination of alkynes, homocoupling and cross-coupling of carbonyl compounds, and aldol reaction . Recently, we found that titanium tetrachloride demonstrates a prominent dehydration effect in the condensation reaction of 1,4-diketones for the synthesis of furans .…”
Section: Introductionmentioning
confidence: 99%